The Nature of Time - A 21st Century View (JOURNAL OF ADVANCES IN PHYSICS, 2018)
• This article is a logical analysis of historical records and reaches conclusions that are original.• Prior to 1905 it was generally believed that the universe had always existed. The exact age of Earth was not known.• The luminiferous æther theory explained how light was able to propagate through empty space.• In 1930 Alfred Korzybski published his book “Science and Sanity”. In it he originated his aphorism —The Map is not the Territory.• Reality consists of physical reality — the territory— and observed reality — the map.• The Rossi-Hall experiment demonstrated that time dilation occurs physically and cannot be observed directly.• The universe came into existence when the big bang occurred.• When photons came into being, time came into being.• All mechanisms for measuring time experience time dilation.• The big bang caused major changes to science’s understanding of the nature of the universe.• The speed of a photon through space equals a Planck length divided by a Planck time.• We don’t really measure time, what we measure is the effect that time has on the instruments used to measure time.• Everything; in Relative Time is based on observers. If you remove all references to observers from either Special Relativity or Spacetime there is almost nothing left.• When the concepts of relative time were originated, no thought was given to the possibility that time might consist of both observed time and physical time.• Photons — and the resulting time — came into existence with the big bang• The movement of photons thru spacetime constitutes absolute time• Without events, nothing happens.• Every event has a frame of reference.• ‘Now’ can occur in physical time and in observed time.• A physical event always results in a physical ‘now’.• Every event must have a frame of reference.• Objects that move through space experience time dilation but they do not observe it.• The observation of each observer is unique for that observer and need not be the same as either the actual event itself or the observation of another observer.• Each observer has his/her own observed ‘now’ which occurs in observer’s frame of reference.• The duration of an observation has no direct relationship to the duration of the event nor need it have the same duration as that of another observer.• Each observer has her/his own frame of reference.• Time dilation is an aspect of physical time, not of observed time.• Observers have no way of knowing that they are experiencing time dilation.• The Lorentz transformation factor ‘?’ is computed by dividing ‘v2’ which is a vector by ‘c2’ which is scalar. Both terms should be scalar. • Both ‘v’ and ‘c’ use clocks to determine their value and all clocks are subject to time dilation.• The Lorentz transaction is supposed to measure ‘?’ but ‘?’ is an element of the calculation!